Moscow's "turn to the East" and challenges to Russia–South Korea economic collaboration under the New Northern Policy. Issue 2 (July 2019) - Rinna, Anthony V.
The Republic of Korea (ROK) has not traditionally regarded the Russian Federation as an important partner in the Korean security crisis. Nevertheless, the ROK–Russia relationship has grown by leaps and bounds. Furthermore, the Moon Jae-in administration's "New Northern Policy, " which focuses especially on economic collaboration with Russia, exhibits a great deal of compatibility with the "turn to the East" in the Russian Federation's recent foreign and domestic policies. For Seoul, the "New Northern Policy" is not simply a means of generating economic benefits for the ROK but is also part of Seoul's plans for promoting peace on the Korean Peninsula. Indeed, the Kremlin shares with South Korea not only the goal of increased economic interconnectivity but also a lasting peace on the Korean Peninsula. Nevertheless, two main barriers exist undermining aims outlined in the New Northern Policy. The continuation of the crisis over North Korea's weapons of mass destruction (WMD) capabilities, particularly the perpetuation of the various layers of sanctions against Pyongyang, frustrate the economic integration as espoused in the New Northern Policy. Furthermore, economic conditions within Russia, namely, a lack of economic development within the Russian Far East, frustrate South Korean hopes for greater trade connectivity with Russia. Substantial changes to both the Northeast Asian sub-regional order as well as in the Russian Federation's domestic economic situation, therefore, are necessary before the prospects envisioned in Seoul's New Northern Policy can be realized.